The evolutionary design of a community information service knowledge network - Yon, Shukriah; Md Daud, Ruzaif Adli; Mat Isa, Azman; Wan Abdullah, Wan Abdul Malek (2008)
Knowledge Management (KM) and knowledge sharing are important factors that support community lifelong learning.The concept of a Community Information Service (CIS) (Kempson, 2000) is attractive in drawing together people whose work shares similar aspects, and consideration is given here to how technology can be used to develop and support such a community.In this paper, concepts from the Community Information Service literature are used to consider the development of a software environment for people working as a community in the area of lifelong learning. The intention was to design the system in an evolutionary way, using a minimal set of essential elements which would be elaborated according to user feedback. Three key design questions are considered: Who can contribute resources to such a system? What happens to existing practices? How is the community engaged?